Disease Modifying Anti-rheumatic Drugs (DMARDs) (Bangladesh Journal of Child Health, 2018)
Disease modifying anti-rheumatic drugs (DMARDs) is a group of drugs that slow or stop the immune system from destroying the joints. Evidence shows Methotrexate is superior to conventional treatment (NSAIDs and/or intra-articular corticosteroids). Among children who have responded to a biologic DMARD, randomized discontinuation trials suggest that continued treatment decreases the risk of having a flare. Although these studies evaluated DMARDs with different mechanisms of action (hydroxychloroquine, azathioprine, sulfasalazine, methotrexate, leflunomide, cyclosporine, etanercept, tocilizumab, infliximab, anakinra, rituximab). There are few direct comparisons of DMARDs.There are insufficient evidence to determine whether any specific drug or group of drugs has greater beneficial effects. Adverse events are found similar between DMARDs.Limited data suggest that short-term risk of cancer is low. Future trials are needed to evaluate the effectiveness of DMARDs against both conventional therapy and other DMARDs in different pediatric rheumatic diseases.Bangladesh J Child Health 2018; VOL 42 (2) :79-85